2007
DOI: 10.1007/s00442-006-0610-1
|View full text |Cite
|
Sign up to set email alerts
|

Maternal androgens in the pied flycatcher: timing of breeding and within-female consistency

Abstract: Maternal hormones can have substantial phenotypic effects in the progeny of many vertebrates. It has been proposed that mothers adaptively adjust hormone levels experienced by particular young to optimize their reproductive output. In birds, systematic variation in egg hormone levels has been related to different female reproductive strategies. Because in many bird species prospects of the offspring change seasonally and with brood number, strategic adjustment of yolk androgen levels would be expected. To test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 56 publications
3
35
1
1
Order By: Relevance
“…Our results show that between-female differences are quite consistent over time and are only to some extent likely to be influenced by environmental challenges. Our repeatability estimates closely resemble the ones found for yolk A4 and T levels in a recent study by Tobler et al (2007) on Pied flycatchers Ficedula hypoleuca. Although their data describe hormone levels of successive clutches, laid within two weeks of each other during a single breeding season, not across two seasons as in our study, they also showed large inter-female variation in yolk androgen levels and a remarkable consistency within individual females.…”
Section: Within-female Consistency Of Yolk Androgen Levelssupporting
confidence: 87%
“…Our results show that between-female differences are quite consistent over time and are only to some extent likely to be influenced by environmental challenges. Our repeatability estimates closely resemble the ones found for yolk A4 and T levels in a recent study by Tobler et al (2007) on Pied flycatchers Ficedula hypoleuca. Although their data describe hormone levels of successive clutches, laid within two weeks of each other during a single breeding season, not across two seasons as in our study, they also showed large inter-female variation in yolk androgen levels and a remarkable consistency within individual females.…”
Section: Within-female Consistency Of Yolk Androgen Levelssupporting
confidence: 87%
“…An alternative prediction is that, if yolk androgen transfer is costly for the females, females receiving food supplementation should be able to transfer higher levels of hormones in the eggs. Th is seems unlikely in our study system, however, since in pied fl ycatchers females naturally in good condition seem to transfer lower levels of androgens in eggs (Tobler et al 2007). 2) We further predicted that the within-clutch hormone transfer pattern would be aff ected by food supplementation: fed females may allocate more androgens to the last egg to counteract hatching asynchrony, thus increasing the survival probability of the later hatched chicks.…”
Section: Ev-2mentioning
confidence: 96%
“…In particular, altricial birds can produce a distinct pattern of yolk androgen concentrations within a single clutch (Schwabl, 1993;Eising et al, 2001) as well as between successively laid clutches (Schwabl, 1997;Gil et al, 2006;Tobler et al, 2007). This between-clutch pattern of yolk androgen deposition was not investigated in free-living precocial birds yet but a decline of yolk testosterone (T) concentrations was found between the early and the latest stages of the first reproductive cycle in domestic species (Okuliarova et al, 2011a;Guibert et al, 2012).…”
Section: Introductionmentioning
confidence: 95%